Clovamide and rosmarinic acid induce neuroprotective effects in in vitro models of neuronal death - Silvia Fallarini; Gianluca Miglio; Tiziana Paoletti; Alberto Minassi; Angela Amoruso; Claudio Bardelli; Sandra Brunelleschi; Giovanni Lombardi (2009)
Phenolic compounds exert cytoprotective effects; our purpose was to investigate whether the isosteric polyphenolic compounds clovamide and rosmarinic acid are neuroprotective.